DAKWAH DAN PERDEBATAN PLURALISME AGAMA - Hamiruddin Hamiruddin (Fakultas Dakwah dan Komunikasi, 2019)
Da'wah is an activity to spread Islam at the same time as an effort to answer various Islamic problems that require the maximum possible effort in carrying it out. But in the midst of these efforts, there are still many challenges that must be faced, one of which is the issue of religious plurality debate. This paper tries to formulate the da'wah and debate of religious pluralism and then offer an alternative solution. Therefore this paper raises the issue of the debate on religious pluralism that is being faced by Muslims today and the preaching solution to the problems of the people. The discussion begins by identifying the problem, then formulating the preaching solution to the problems of the people in the form of preaching through a strategic da'wah format by emphasizing the increase in preaching resources in explaining the teachings of pluralism in Islam as something that has become sunnatullah in the life of mankind.